The end of nostalgia : Mexico confronts the challenges of global competition - Negroponte, Diana Villiers (Brookings Institution Press, 2013)
This book explores how Mexico, in transition from one-party rule to liberal democracy, can develop the institutional and cultural underpinnings needed to meet the challenges of global economic competition. The contributors examine education, energy, domestic politics, regional trade and investment, public security, and relations with the United States. --